Hubungan Kemampuan Mengajar Guru Dan Minat Belajar Siswa Dapat Meningkatkan Hasil Belajar) Bahasa Arab Di MTsN 1 Palembang - Nazarmanto Nazarmanto; Suryati Suryati (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
This research was intended to know the relationship between teacher’s teaching ability and student interest in learning with the result of student study in the Arabic subject regilious school (MTs) N 1 palembang. This research hypothesis is: (1) there is a significant positive link between teacher teaching ability and student learning in Arabic subject religious school (MTs) N 1 palembang; (2) there is a significant positive relationship between a student's interest in learning and the result of a student's study in the Arabic subject religious school (MTs) N 1 palembang; (3) there is a significant positive link between a teacher's teaching ability and a student's interest in learning simultaneously (together) with the result of the student's learning in the Arabic subject MTSN 1 palembang. The study was conducted at  MTSN 1 palembang with the respondents of 1 Arabic teacher and the students of religious school (MTs) N 1 palembang of 35 (for samples). The study employs qualitative and quantitative approaches. Quantitative data analysis uses regression and partial correlation (simple) and simultaneous correlation (double) with the help of the SPSS program. Qualitative data analysis follows the techniques presented by Miles and Hubermen (1992:16-19), which are data reduction, data presentation, and a deduction/verification drawing. Studies indicate that: (1) there is a positive link between a teacher's teaching ability and that of a student in the Arabic subject religious school  (MTs) N 1 palembang. Students' learning in Arabic subjects can be influenced by teacher teaching ability, at religious school ( MTs) N 1 palembang is a large influence of only 3.1%, (2) there is a positive link between student learning interests and student learning in the arabic launguage religious school (MTs) N 1 palembang. The results of a student's learning in an Arabic subject MTSN 1 palembang can be influenced by a student's interest in learning. The magnitude of the influence of the interest in MTSN 1 palembang is 30.6%, (3) there is a positive link between a teacher's teaching ability and a student's interest in learning together in the Arabic subject MTSN 1 palembang. The result of students' learning in the arabmtsn 1 palembang can be influenced by a teacher's teaching ability and a student's interest in learning together. The impact of MTSN 1 palembang is 34.7%, of which 66.3% is affected by other factors. That is, if teacher teaching ability and student learning interests increase students' learning results will increase, and if the teacher's teaching ability and student learning interests decline then the student's learning results will also decline.